The Anatomy of Leadership in Industry 4.0 : The 4.0D® Leadership Development Model. - Uys, Johann. (Knowledge Resources, 2021)
With the large-scale advent of the 4th Industrial Revolution (4IR), the world is in constant flux. This has been exacerbated by the fallout of Covid-19. To be relevant in the next few decades, any business that wants to develop their leadership cadres will have to embrace drastic transformations in their approach to every area of leadership formalisation, modelling, training and development._x000D__x000D_This newly developed 4.OD® Leadership Development Model is the departure point for business to embark on new leadership journeys appropriate for the future. The new leadership skills required are comprehensively addressed._x000D_The model will become one of the main contributors in the field of future business leadership and leadership preparedness for Industry 4.0 for most organisations._x000D__x000D_4.OD® Leadership Development Model is scientifically based within the context of organisations and business._x000D_The Anatomy of Leadership in Industry 4.0 is a detailed exposition of the model, the technical and dynamic aspects of the model application as well as the implications for leadership in business.